Clinical Features and Mutation Analysis of Gordon Holmes Syndrome Associated with RNF216 Gene Mutation and a Literature Review - CHEN Meiping; YANG Hongbo; PAN Hui; FENG Feng; ZHU Yicheng; ZHU Huijuan (罕见病研究, 2023)
Objective To summarize the clinical characteristics and RNF216 gene mutation of a patient with Gordon Holmes syndrome (GHS), and to improve the understanding of the genetic and clinica characteristics of this disease through literature review. Methods We collected the clinical data of the patient with GHS, extracted the DNA from 2 mL peripheral venous blood of the patient and his parents for whole exome gene detection, and then we analyzed the clinical and genetic characteristics of all previously reported patients with RNF216 gene mutation. Results The young male patient was short in stature at sixyearsold and was diagnosed growth hormone deficiency.He had no secondary sexual characteristics by the age of 15 and was diagnosed hypogonadal hypogonadism.After the age of 22, he gradually developed abnormal gait and had progressive decline in speech, motor, and cognitive functions.Whole exome sequencing revealed a homozygous, nonsense mutation c.1549C>T (p.R517*) in the RNF216 gene.His parents were consanguineous and were heterozygous carriers of the mutations with phenotypic normality.Combined with literature review and this case report results showed that a total of 21 patients of the disease in the world and among them 15 had pathogenic variants of RNF216 gene mutation.7 of the 15 had truncated mutations, 5 had missense mutations, and 1 synonym mutation, 1 splice mutation, and 1 deletion mutation respectively.RNF216 gene mutation can be seen in neurodegenerative diseases with multiple overlapping symptoms of GHS, Huntington-like disease, and 4H syndrome.The main clinical manifestations are hypogonadotropic hypogonadism and early-onset progressive neurological dysfunction in adolescence or early adulthood.The median age of onset of neurological symptoms is 28 years old, featuring cerebellar ataxia, dysarthria, and cognitive impairment, as well as imaging manifestations of extensive white matter lesions and cerebellar atrophy. Conclusions The mutation of RNF216 gene can cause GHS.Genetic testing is helpful to the diagnosis and treatment of rare diseases.